IMPLEMENTASI SISTEM OTOMASI PERPUSTAKAAN BERBASIS LARIS (LIBRARY AUTOMATION RETRIEVAL INFORMATION SYSTEM) - Enik Matul Khoiriyah; Mohammad Syahidul Haq (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2020)
This study aims to describe and analyze the implementation of library automation systems, the role of librarians, benefits, and constraints of the implementation of library automation systems at the Airlangga University Library Surabaya. This study used a qualitative approach with a case study research design. The technique of collecting data uses interviews, observation and documentation studies. The data analysis technique in this study uses an interactive model that continues continuously to completion. Data analysis activities include: data condensation, data display, and conclusion drawing / verification. The results showed that: (1) the implementation of the library automation system was carried out through several stages, namely: the software installation process, the procurement process, cataloging, data input processes, and circulation process. (2) the role of librarians in the implementation of library automation systems provides user education to users, filtering and presenting information that fits the needs of users and can be accounted, and helps users in searching library materials. (3) the benefits of implementing the library automation system include improving service quality, facilitating the data input process, streamlining energy and time, simplifying the checking process, improving the image or quality of libraries and universities, enhancing cooperative relationships. (4) the constraints on the implementation of the library automation system are the occurrence of a power outage, the occurrence of errors when inputting data, the incompatibility of information on book data on the system. Efforts to overcome the obstacles to the implementation of the library automation system are to coordinate with the Information Technology and Directorate of Information Systems, provide UPS and generator tools, and cross check data to minimize data input errors.